RETRACTED: Development of a mathematical model of the process of mixing liquid feed in an experimental setup and optimization of design parameters - Solonshchikov Pavel; Savinykh Petr; Aleshkin Alexey; Kipriyanov Fedor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001